Mothering Practices in Cambodia: Making Sense of Physical Disciplining (Journal of Comparative Social Work, 2021)
The physical disciplining of children is widespread globally. To work towards ending physical disciplining, we need to understand this practice’s local and contextual justifications. In this article, we explore Cambodian mothers’ rationale for the physical disciplining of their children, as we seek to address two questions: 1) How do Cambodian mothers perceive physical discipline?, and 2) How do they negotiate and justify physical disciplining practices? Based on 10 group interviews with mothers of small children, and in different communities in Cambodia, we found that the physical disciplining is a common practice used to correct behaviours considered unhelpful, impolite or disrespectful. However, there are ambivalent attitudes toward this. This suggests that physical discipline is not a static practice, but rather one that is constantly negotiated. We argue that Barbara Rogoff’s concept of cultural scripts for parenting is well suited for making sense of how physical discipline is justified among Cambodian mothers.